ACCOUNTING AND ANALYTICAL SUPPORT OF THE WAR’S IMPACT ON THE SUSTAINABLE DEVELOPMENT GOALS ACHIEVEMENT EVALUATION - KRUTOVA, Anzhelika; NESTERENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Introducing of organizational and methodological tools of accounting and analytical support developing for assessing the impact of war on achieving of the Sustainable Development Goals and working-out of practical recommendations on its use both at the national level and at the level of economic entities is the purpose of the article. The influence of Russian aggression on achieving of the Sustainable Development Goals both by Ukraine and the whole world is analyzed. The main challenges that Ukraine will face in the preparation of a Voluntary National Review during and after the war are identified, namely: the complexity of information collection, including monitoring, evaluation of Russian invasion negative economic effects on the world; the general availability of data, and specific difficulties of disaggregated and alternative data collection on evaluation the impact of Russo-Ukrainian war on Ukrainian and world’s economy; coordination of national strategies of resource mobilization for economic damage overcoming; challenges related to aligning institutions, institutional capacity formation, effective governance, decentralization, ensuring policy coherence etс. It is proven that accounting system produces a significant volume of information flows circulating in the globe. It was determined that a significant place in the process of accounting and analytical support formation at the corporate level is occupied by the development of metric systems and methods of evaluating financial and non-financial indicators, which allow evaluation of a company’s activities results as accurately and reliably as possible from point of view of various aspects. Accounting and analytical systems provide basis for Sustainable Development Goals indicators determining at national level. In order to form reliable accounting and analytical support for determining the impact of war on identified by UN 183 indicators of sustainable development it is proposed to adapt the methodology, which is based on the war economic destruction level simulator methodology, which is based on natural disasters vulnerability evaluation model and involves determination of a number of key indicators, such as: the war damage level rate; the armed attacks intensity rate, the war destruction magnitude rate, the inflation and unemployment levels in war ratio. In order to adapt the proposed methodology, it is recommended to calculate the rate of the war impact on the Sustainable Development Goals achievement over the past ten years, which corresponds to the 2030 Agenda for Sustainable Development and the period during which Ukraine suffers from the Russian aggression. Implementing the proposed methodology of the war negative economic, social and ecological effects measuring could be used to create an informational basis for the most effective recovery of our country and will be of service for formation of an effective system of evaluation the impact of the war on the SDGs achievement at both national and global levels.